The aesthetic treatment for anterior teeth with lost crown by endorestoration - Nanik Zubaidah (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: The aesthetic has an important role in social life, especially the anterior teeth. The aesthetic abnormality of anterior teeth i.e. discoloration, malpotition or the anterior teeth with crown damage for more than one third or all part of crown is lost due to caries or other causes, will influence its appearance especially during smile. Purpose: The aim of this case report, therefore, is to show how teeth with clinical crown lost or only the root left still can be treated by endorestoration treatment in order to reconstruct the shape and function of the teeth similar to the original ones. Case: Female 52 years old with the lost crown of anterior teeth. The patient did not want her teeth to be extracted. Case Management: The abnormality of these teeth are still able to be reconstructed by endorestoration i.e. endodontic treatment with post and core insertion in the root canal will increase its retention and recovery by the porcelain crown fused to metal to recover the original formation and aesthetic and thus has the normal refunction. The treatment, it improve the confidence of the patient, and also can function normally. The patient did not feel pain. Ronsenography showed the periapical lesion diminished, the neighbor gingival was going better in both function and color. Conclusion: Endorestoration treatment on the anterior teeth with lost crown could recover the normal function, dental aesthetic and self confidence.